(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Low back pain in postnatal women is a major issue. So, lumbar curvature is a key feature to maintain core strength for which it has to be assessed. The individual variations in spinal curvature and lordotic pattern signifies the bio mechanics of the spine and it responds according to the load / activities. To find out the pre-test measures of flexibility, functional capacity and discomfort level related to lumbar spine in the subjects with postural dysfunctions. To find out the post-test flexibility, functional capacity and discomfort level in the subjects with postural dysfunctions. To analyze the difference between the pre-test and post-test values. People should also have awareness about the posture maintenance. So, early assessment is necessary. Also secondary factors like the type of shoes wear, Occupation and Lifestyle can influence the spinal curvatures which can be dealt with easier with the outcome of the research. Methodology: In this experimental study, 29 people with age group of 25 to 60 years who have chronic low back pain. Their lumbar spine flexibility, functional capacity, and discomfort level was measured pre-test and post-test. Results were obtained and compared. Result: The average mean value of lumbar spine flexibility pre-test measured with schober test was 1.81 while post-test was 2.08. Average mean value of VAS for lumbar spine was 6.06 while post-test was 3.24. Average mean value for pre-test functional capacity measured with 6 min walk test was647.58 while post test was 665.17. Conclusion: On comparing summary score of lumbar spine flexibility, VAS, and functional capacity, the differences showed were 0.27 cms, 2.82, 17.59 metres respectively. So, we can conclude that there was a signicant difference in the improvement of lumbar spine flexibility, functional capacity and also decrease in pain after the treatment.